Detection and Analysis of CO, CO2 Exhaust Emissions in Two-Wheeled Motorized Vehicles - Suryadi, Kusno; Fazzry, Burhan (PROtek : Jurnal Ilmiah Teknik Elektro, 2023)
CO and CO2 are some of the exhaust gases resulting from the combustion of motor vehicles. The increase in the number of vehicles causes the concentrations of CO and CO2 exhaust gases in the air to increase. To be able to detect the amount of CO gas concentration using the MQ7 sensor and the CO2 sensor, the TGS4161 sensor is used. For the sensor to work properly, it needs a normalization process before it is applied to the testing stage. Based on the test results, the sensor normalization process requires 54 seconds with a maximum CO gas concentration of 4139.7 ppm, or 0.413%, and an output voltage of 4.39 volts. The CO2 exhaust gas test resulted in a maximum gas concentration of 5862.06 ppm, or 0.586%, with an output voltage of 0.51 volts. From several test results, the amount of exhaust gas concentration is dominantly determined by the type of vehicle and engine speed, while the type of fuel does not significantly affect the exhaust gas concentration, with an average percentage difference of 1.2%..